Ideal mortar composition with rice husk ash addition and addictive for maximum mortal strength - Rusnardi Rahmat Putra (invotek, 2021)
The intensity of earthquakes increases from time to time both in number and in strength; recently, in Indonesia, damage to buildings by earthquake acceleration usually begins with damage to walls. Besides having a function as a barrier between spaces in construction, walls also have an essential role in increasing a building structure's rigidity. Mortar, which is usually used as a wall and plastering, has a role as a binder between the walls themselves' components so that quality mortar will help the walls be stronger. This research aims to produce the ideal mortar mixture with low price, high quality, and easy to obtain material. The proposed added composition was husk ash and Fosroc SP 337 additive, varied based on cement's weight. The yield of mortar with added ingredients will be compared with ordinary mortar without added ingredients. The specimens' manufacture used 20 samples of 5cm x 5cm x 5cm cubes with five variations of mortar composition, and mortar compressive strength testing was carried out at 7, 14, and 28 days of age. The maximum compressive strength obtained for mortar with the addition of 15% rice husk ash, 1% fosroc sp 337, and the combination of the two experienced an increase in the compressive strength value, the ratio of the average compressive strength of the mortar, the highest average compressive strength results in the mixture 1 PPC cement: 4 Sand with the addition of 15% rice husk ash: 1% fosroc sp 337 with an average compressive strength yield of 116.6 kg / cm² at the age of 7 days, 145.6 kg / cm² at the period of 14 days and 154.6 kg / cm² at the age of 28 days.